EFEK PEMBERIAN INSENTIF DAN KOMITMEN DALAM UPAYA PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PT GELAEL SUPERMARKET MAKASSAR - Andi Siti Raodahtul Jannah; Edy Jumady (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This study aims to analyze: (1) the effect of providing incentives to employee work productivity, (2) the effect of commitment to employee work productivity, (3) the effect of intuitive and commitment to the work productivity of employees of PT. Gelael Supermarket. This research is a descriptive quantitative research. The study population was all employees of PT. Gelael Supermarket as many as 150 employees with a sample of 65 respondents. Data collection using questionnaires and interviews, the sampling technique is simple random sampling, while the data analysis is done using multiple linear regression analysis. Results of the study: 1) Incentives had a significant positive effect on employee work productivity. 2) Commitment has a positive and significant effect on employee work productivity. 3) Simultaneous incentives and commitments affect employee work productivity.